Comparative Analysis of Financial Report Processes Manually and Using Computer Accounting Applications - Adinegara, Ahmad Andi (Journal of Business, Accounting and Finance, 2024)
Manual accounting systems are simple and easy to understand, suitable for small businesses, but are often suboptimal and slow. Manual documents are often incomplete, do not have serial numbers, and do not comply with general standards, so the process is long and financial reports are difficult to produce quickly when needed. For large companies, computer accounting systems are more effective and productive. This technology significantly influences company management, especially in decision making and preparing financial reports. Use of technology includes hardware, software and other supporting applications. Accountants need to adapt to new, more analytical roles, maintain data security, keep up with regulatory changes, and continually improve technology skills. The use of computer applications in accounting helps with recapitulation, reduces workload, and allows for more efficient reporting on a large scale, increasing organizational productivity and effectiveness.